Health consequences of an elite sporting career: Long-term detriment or long-term gain? A meta-analysis of 165,000 former athletes - Runacres, A.; Mackintosh, K. A.; McNarry, M. A. (Sports Medicine, 2021)
Introduction: Exercise is widely accepted to improve health, reducing the risk of premature mortality, cardiovascular disease (CVD) and cancer. However, several epidemiological studies suggest that the exercise-longevity relationship may be `J` shaped; with elite athlete`s likely training above these intensity and volume thresholds. Therefore, the aim of this meta-analysis was to examine this relationship in former elite athletes. Methods: 38,047 English language articles were retrieved from Web of Science, PubMed and SportDiscus databases published after 1970, of which 44 and 24 were included in the systematic review and meta-analysis, respectively. Athletes were split into three groups depending on primary sport: Endurance (END), Mixed/Team, or power (POW). Standard mortality ratio`s (SMR) and standard proportionate mortality ratio (SPMR) were obtained, or calculated, and combined for the meta-analysis. Results: Athletes lived significantly longer than the general population (male SMR 0.69 [95% CI 0.61-0.78]; female SMR 0.51 [95% CI 0.40-0.65]; both p < 0.01). There was no survival benefit for male POW athletes compared to the general population (SMR 1.04 [95% CI 0.91-1.12]). Although male athlete`s CVD (SMR 0.73 [95% CI 0.62-0.85]) and cancer mortality (SMR 0.75 [95% CI 0.63-0.89]), were significantly reduced compared to the general population, there was no risk-reduction for POW athletes CVD mortality (SMR 1.10 [0.86-1.40]) or END athletes cancer mortality (SMR 0.73 [0.50-1.07]). There was insufficient data to calculate female sport-specific SMR`s. Discussion: Overall, athletes live longer and have a reduced incidence of both CVD and cancer mortality compared to the general population, refuting the `J` shape hypothesis. However, different health risks may be apparent according to sports classification, and between sexes, warranting further investigation.